Determinant of Islamic banking institutions' profitability in Malaysia - Idris, Asma' Rashidah; Abu Hassan Asari, Fadli Fizari; Abdullah Taufik, Noor Asilah; Salim, Nor Jana; Mustaffa, Rajmi; Jusoff, Kamaruzaman (IDOSI Publications, 2011)
Starting with the establishment of the Malaysia’s first Islamic bank namely Bank Islam Malaysia Berhad (BIMB) in 1983, the Islamic banking system has shown better development and is now widely accepted by Muslims as well as non-Muslim in this country. Islamic Banking System which follows the rule of Shariah plays a vital role in Malaysia as its profitability contributes to the growth of the economy. Therefore, this study was conducted in order to examine the determinants of profitability for Islamic Banking Institutions in Malaysia which are listed on the Bursa Malaysia. The bank-specific determinants (internal factors) include capital adequacy, credit risk, liquidity, bank size and management of expenses. The methodology employed is the Generalized Least Square (GLS) panel data analysis, using quarterly data from nine Islamic banks, which consist of foreign and local Islamic banks incorporated in Malaysia for the period 2007-2009. The result revealed that only the bank size is significant in determining the profitability with positive relationship. It is to be concluded then that, even though there is a lot of determining factors, only the bank’s size may put confidence in the eyes of the consumers. For the future studies, it is recommended to have a wider scope where other Malaysian Islamic financial institutions and more determinant factors can be taken into account.